(untitled) (Revista revoluciones, 2023)
This article examines the mechanisms used to finance the liberation expedition of General José de San Martín to Peru. In this context, the investigation will analyze the details that contributed to the constitution of the association of Chilean and River Plate merchants that provided funds to the San Martin company. Furthermore, this will also serve to identify the participants and point out the benefits they received from this commercial concert.